2018
DOI: 10.1101/342923
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AlleleAnalyzer: a tool for personalized and allele-specific sgRNA design

Abstract: 15The CRISPR/Cas system is a highly specific genome editing tool capable of distinguishing alleles differing 16 by even a single base pair. However, current tools only design sgRNAs for a reference genome, not taking 17 into account individual variants which may generate, remove, or modify CRISPR/Cas sgRNA sites. This 18 may cause mismatches between designed sgRNAs and the individual genome they are intended to target, 19 leading to decreased experimental performance. Here we describe AlleleAnalyzer, a tool fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…While this manuscript was being prepared, a few web-servers that design gRNAs specifically for targeting SNVs across the genome, especially in an allele-specific manner have been reported in the literature (6265). These present an important advancement towards gRNA design for precision medicine in general.…”
Section: Discussionmentioning
confidence: 99%
“…While this manuscript was being prepared, a few web-servers that design gRNAs specifically for targeting SNVs across the genome, especially in an allele-specific manner have been reported in the literature (6265). These present an important advancement towards gRNA design for precision medicine in general.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, allele-specific correction may be the most suitable approach. To this end, the Pollard lab developed a new software, AlleleAnalyzer, to facilitate allele-specific gRNA design ( Keough et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, AlleleAnalyzer, a bioinformatic tool was reported to target SNPs by obtaining sequences data from the 1,000 Genomes project. By utilizing disease-associated haplotypes, AlleleAnalyzer designs allele-specific dual gRNAs ( Keough et al, 2019 ). Scott and Zhang (2017) and Lessard et al (2017) also developed bioinformatic tools to design gRNAs that target conserved genomic loci to avoid gRNA incompatibility due to genetic variations.…”
Section: Snp-derived Pammentioning
confidence: 99%